Characterization of phyto-components with antimicrobial traits in supercritical carbon dioxide and soxhlet Prosopis juliflora leaves extract using GC-MS - Nagaraj M. Naik; M. Krishnaveni; M. Mahadevswamy; M. Bheemanna; Udaykumar Nidoni; Vasant Kumar; K. Tejashri (Scientific Reports, 2023)
Abstract This study aimed to screen the bioactive compounds from Prosopis juliflora leaf supercritical fluid extract and to assess its antimicrobial properties. Supercritical carbon dioxide and Soxhlet methods were used for extraction. The extract was subjected to Gas Chromatography-Mass Spectrometer (GC-MS) and Fourier Transform Infrared for the characterization of the phyto-components. When compared to soxhlet extraction, more components (35) were eluted by supercritical fluid extraction (SFE), according to GC-MS screening. Rhizoctonia bataticola, Alternaria alternata, and Colletotrichum gloeosporioides were all successfully inhibited by P. juliflora leaf SFE extract, which demonstrated strong antifungal properties with mycelium percent inhibition of 94.07%, 93.15%, and 92.43%, respectively, compared to extract from Soxhlet, which registered 55.31%, 75.63% and 45.13% mycelium inhibition respectively. Also, SFE P. juliflora extracts registered higher zone of inhibition 13.90 mm, 14.47 mm and 14.53 mm against all three test food-borne bacterial pathogens viz Escherichia coli, Salmonella enterica and Staphylococcus aureus respectively. Results obtained from GC-MS screening revealed that SFE is more efficient than soxhlet extraction in recovering the phyto-components. P. juliflora may provide antimicrobial agents, a novel natural inhibitory metabolite.